2021
DOI: 10.3390/v13071402
|View full text |Cite
|
Sign up to set email alerts
|

Impact of HCV Eradication on Lipid Metabolism in HIV/HCV Coinfected Patients: Data from ICONA and HepaICONA Foundation Cohort Study

Abstract: Objectives: HCV shows complex interactions with lipid metabolism. Our aim was to examine total cholesterol (TC) and low-density lipoprotein cholesterol (LDL-C) changes in HIV/HCV coinfected patients, after achieving sustained virological response (SVR), according to different HCV genotypes and specific antiretroviral use. Methods: HIV/HCV coinfected patients, enrolled in the ICONA and HepaICONA cohorts, who achieved DAA-driven SVR were included. Paired t-tests were used to examine whether the pre- and post-SVR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 37 publications
3
5
1
Order By: Relevance
“…In line with the results of prior studies that included HCV-monoinfected [24][25][26] and HIV/HCV-coinfected participants [27], we noted elevations in total cholesterol, triglyceride, and LDL levels after SVR. HCV is hypothesized to induce hypolipidemia by stimulating LDL receptor expression and modulating proteins involved in liver steatosis [27,28]. HCV eradication may therefore reverse these processes, leading to paradoxical increases in serum lipid levels.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In line with the results of prior studies that included HCV-monoinfected [24][25][26] and HIV/HCV-coinfected participants [27], we noted elevations in total cholesterol, triglyceride, and LDL levels after SVR. HCV is hypothesized to induce hypolipidemia by stimulating LDL receptor expression and modulating proteins involved in liver steatosis [27,28]. HCV eradication may therefore reverse these processes, leading to paradoxical increases in serum lipid levels.…”
Section: Discussionsupporting
confidence: 91%
“…Thirty-four (68%) denied any prior IVDU, while 41 (82%) contracted other sexually transmitted infections (STIs), including syphilis, gonorrhea, and chlamydia, during follow-up (Table 1). The median durations between HCV seroconversion and pre-DAA assessment and between DAA completion and post-DAA assessment were 15 [IQR 9,29] and [27][28][29][30][31][32][33][34][35][36][37][38] weeks, respectively. The predominant DAA regimens used were sofosbuvir/ledipasvir (52%) and sofosbuvir/velpatasvir (36%).…”
Section: Resultsmentioning
confidence: 99%
“…34 In fact, HCV infection is related to "viral" steatosis and hypolipidemia (low TCOL and LDL-C with near normal TG and HDL-C), which were shown to rapidly reverse after SVR with both IFN and DAAs. 31 On the other hand, HCV clearance is associated with a worsening lipid profile, 35,36 but it is not clearly understood if this change could be associated with an increased risk of atherogenesis. 37 To date, the CV risk in subjects with HCV after therapy with DAAs is still debated, and the evidence among the subgroup of patients with T2DM is even more scarce or quite absent.…”
Section: Discussionmentioning
confidence: 99%
“…HCV infection has been described as a contributor to poor immunological recovery in PLWH. However, a recent study in the context of the ICONA and HEPA-ICONA observational cohorts showed that HCV eradication following DAA treatment does not have an impact on CD4+ T cell recovery in PLWHIV [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is known that HCV alters lipid pathways to enhance its replication. HCV infection could cause hypocholesterolemia; therefore, successful treatment may lead to elevation of cholesterol, including LDL-cholesterol [ 26 ]. Indeed, several studies reported pro-atherogenic lipid changes in patients with SVR [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%